Markets, Businesses, and Consumption in Refugees Settlements: A Review and F view and Future Resear e Research Trajectory - Beninger, Stefanie (International Society of Markets and Development, 2022)
The global refugee crisis is increasing, and many refugees will end up living in refugee settlements, also known as refugee camps. These settlements have dynamic economic activities, and such activities deserve attention. This paper draws upon academic and practitioner work to describe pertinent aspects of consumption, businesses, and markets in these settlements, including in relation to multiple stakeholders. These stakeholders can include, for example, governments, aid agencies, private sector, and local community groups. Based on these insights, the paper identifies key theoretical areas in need of attention related to these economic activities in refugee settlements, including market change, resilience, and vulnerability, and delineates an ambitious research trajectory for the future.
Keywords: 53 Ciencias Económicas; ODS 10 - Reducción de las desigualdades